How did they do it? Incorporating discovery elements in science texts - Soares, S.; Jerónimo, R.; Kolinsky, R.; Morais, J. (XV PhD Meeting in Psychology, 2019)
Although scientific literacy is fundamental for social progress learning and teaching science can pose a challenge. Previous studies show that presenting scientific contents through narratives, compared to expository texts, can produce better learning results with middle and high school students (e.g., Arya & Maul, 2012; Hadzigeorgiou et al., 2012). In this project we will investigate how discovery narratives (vs. expository text) impact the science learning of university students by looking at different levels of comprehension (recall of explicitly stated information, inferencing, understanding key ideas and applying key ideas in a novel situation). Two pairs of scientific texts and respective learning measures have been built in collaboration with linguistics and science experts and are being tested through a qualitative pilot study and a preliminary experimental study. The qualitative study consists in think aloud interviews, conducted while participants read the texts and complete the learning measures, with the goal of accessing mental processes during task completion. In the experimental study, participants read the texts, evaluate them on a set of parameters (e.g., difficulty, interest, coherence) and complete the learning measures and complementary reading, knowledge and comprehension measures; the goal is to test the impact of text format in the different levels of comprehension and its relation with the complementary measures. The results from these studies will be presented and the next steps and the implications of the project discussed. We hope to shed light on the impact of different formats in science learning and to inform science learning practices.